Resiliensi Ekonomi Keluarga: Manajemen Sumber Daya Pada Masa Ketidakpastian - Syifa Salsabila; Yani Achdiani (JURNAL MULTIDISIPLIN ILMU AKADEMIK, 2026)
This family economic resilience study examines resource management strategies during uncertainty periods like economic crises and pandemics. The objective is to identify key factors enabling families to maintain stability and adapt effectively. Using a mixed-methods approach with surveys and interviews among 200 Indonesian families in West Java, the research reveals that diversified income sources, prudent financial planning, and strong social support networks are critical. Findings show resilient families reduce vulnerability by 35% through adaptive budgeting and community collaboration. These insights offer practical implications for policymakers to enhance family support programs and promote sustainable economic practices.